2020
DOI: 10.1007/s00330-020-07497-y
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating anemia using contrast-enhanced spectral detector CT of the chest in a large cohort of 522 patients

Abstract: Objectives The blood of patients with anemia demonstrates distinctly lower attenuation in unenhanced CT images. However, the frequent usage of intravenous contrast hampers evaluation of anemia. Spectral detector computed tomography (SDCT) allows for reconstruction of virtual non-contrast images (VNC) from contrast-enhanced data (CE). The purpose of this study was to evaluate whether VNC allow for prediction of anemia. Methods Five hundred twenty-two patients with CE-SDCT of the chest and accessible serum hemo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 28 publications
4
6
0
Order By: Relevance
“…[ 20 ] Our study showed also a similar results to this work, both in regards to the correlation between hemoglobin levels and CT attenuation of the blood, and the threshold for defining anemia (r = 0.54; HU values of 39.2 and 37.6 for men and women, respectively). [ 20 ]…”
Section: Discussionsupporting
confidence: 86%
“…[ 20 ] Our study showed also a similar results to this work, both in regards to the correlation between hemoglobin levels and CT attenuation of the blood, and the threshold for defining anemia (r = 0.54; HU values of 39.2 and 37.6 for men and women, respectively). [ 20 ]…”
Section: Discussionsupporting
confidence: 86%
“…Anemia is a disorder defined as a reduced absolute number of circulating red blood cells, indicated by a low serum hemoglobin concentration ( 1 ). It occurs when a low number of red blood cells in the circulatory system leaves the oxygen-carrying capacity insufficient to meet physiological needs ( 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…Iron deficiency is the most significant contributor to the occurrence of anemia, which accounts for 50% of the cases. Whereas vitamin deficiencies (folate and vitamin B12), infections, and hemoglobinopathies contribute to the rest of the cases of anemia worldwide ( 1 3 , 5 , 6 ). Lactating women, women of reproductive age, adolescent girls, pregnant women, newborn infants, and young children are the major risk groups for anemia ( 3 , 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…Zhou et al ( 27 ) considered the threshold of IVS-LV at 13.5 HU could obtain high diagnostic performance for severe anemia with the AUCs of 0.908 for men and 0.923 for women, respectively. Zopfs et al ( 29 ) demonstrated that an approximation of serum Hb level and anemia can be conducted based on measurements of the LV and DAo in reconstructive virtual non-contrast (VNC) images. Cutoff values of mild, moderate, and severe anemia in VNC images are 39.2 HU (AUC = 0.857) and 33.6 HU (AUC = 0.879) for men and 37.6 HU (AUC = 0.833) and 32.7 HU (AUC = 0.932) for women, respectively.…”
Section: Discussionmentioning
confidence: 99%